2014
DOI: 10.3389/fgene.2014.00167
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the 3′-UTR of CYP1A2, CYP2B6, CYP2D6, CYP3A4, NR1I2, and UGT2B7: potential effects on regulation by microRNA and pharmacogenomics relevance

Abstract: Introduction: Pharmacogenomics research has concentrated on variation in genes coding for drug metabolizing enzymes, transporters and nuclear receptors. However, variation affecting microRNA could also play a role in drug response. This project set out to investigate potential microRNA target sites in 11 genes and the extent of variation in the 3′-UTR of six selected genes; CYP1A2, CYP2B6, CYP2D6, CYP3A4, NR1I2, and UGT2B7.Methods: Fifteen microRNA target prediction algorithms were used to identify microRNAs p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 71 publications
1
33
0
Order By: Relevance
“…We next sought to determine whether the common SNP rs3100 c.1761 C/T [27] present in the UGT2B15 3’-UTR had an effect on binding of any of the candidate UGT2B15 -regulating miRNAs. Interestingly, in silico analysis using the bioinformatics program miRanda determined that the rs3100 SNP was located within the predicted miR-376c-3p MRE (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next sought to determine whether the common SNP rs3100 c.1761 C/T [27] present in the UGT2B15 3’-UTR had an effect on binding of any of the candidate UGT2B15 -regulating miRNAs. Interestingly, in silico analysis using the bioinformatics program miRanda determined that the rs3100 SNP was located within the predicted miR-376c-3p MRE (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This way we demonstrated that SNP rs10929303 C>T located in the common UGT1A 3’-UTR created a novel MRE for miR-21–3p. Reporter gene assays by another group showed that the UGT2B15 3’-UTR rs3100 c.1761C (reference) allele resulted in lower UGT2B15-dependent luciferase reporter activity compared with the (variant) c.1761T allele in liver, breast, colon, and prostate cancer cell lines [27]. Those authors suggested that this SNP might be located within a miRNA binding site that could influence UGT2B15 expression.…”
Section: Discussionmentioning
confidence: 99%
“…At present, international research on NR1I2 gene polymorphisms focuses only on African Americans and Caucasians, instead of Asians or Chinese. Moreover, NR1I2 mutations differ greatly between the races (Tsuchiya et al, 2004;Wang et al, 2007;Swart and Dandara, 2014). Uno et al (2003) first discovered the NR1I2 promoter region six-base pair deletion mutation (rs3842689, -/GAGAAG), which occurs in a potential liver nuclear factor (HNF-1) binding site.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to CYP1A1 and CYP1B1, CYP1A2 is primarily inducible through aromatic hydrocarbon receptor-mediated transactivation by ligand binding and nuclear translocation [8]. In addition, accumulating evidence indicates that CYP1A2 expression is influenced by genetic polymorphisms [9] and transcriptional factors [8,10]; recently it was been predicted that CYP1A2 may be subject to post-transcriptional regulation by microRNAs (miRNAs) [11]. …”
Section: Introductionmentioning
confidence: 99%
“…They usually bind to their target sequences within the 3′-untranslated regions (3′-UTR) of mRNA molecules, which facilitates mRNA degradation or translational repression [1113]. Some miRNAs have been found to interact directly with CYP450 mRNA transcripts.…”
Section: Introductionmentioning
confidence: 99%